PERANAN RANGKAYO HJ. SYAMSIDAR YAHYA DALAM BIDANG SOSIAL KEMASYARAKATAN DI PEKANBARU - Desi Widia Yanti; Isjoni Isjoni; Bedriati Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Speaking of women in every development era, it is inseparable from a special role that is performed in a society or within the scope of the general public, currently the role of women is needed so that the existence of a woman today brings a very big change in all aspects both within the scope of education, social society, and others. Exemplary from a very influential figure in Riau, especially in the city of Pekanbaru, even his contribution to the establishment and development of this city called the yellow lancing earth, Syamsidar Yahya. The research objectives are 1) To find out the life history of Rangkayo Hj. Syamsidar Yahya 2) To find out the background of the process of the formation of a Social Community institution in Pekanbaru which was established by Rangkayo Hj. Syamsidar Yahya, 3) To find out the role of Rangkayo Hj. Syamsidar Yahya in social society in Pekanbaru, 4) To find out the development of social social institutions formed by Rangkayo Hj. Syamsidar Yahya in Pekanbaru. The results of this study Rangkayo Hj. Syamsidar Yahya Born on November 11 in Nagari Batagak Bukittinggi West Sumatra 1914 and died in 1975 when he was 61 years old. Rangkayo Hj. Syamsidar Yahya was born to H. Yahya and Siti Rafiah. Rangkayo Hj. Syamsidar Yahya is one of the women leaders from West Sumatra who devoted herself and the struggle for the Riau region and in particular Pekanbaru in addition to her role in her entire life for the women's movement.Key Words: Rangkayo Hj. Syamsidar Yahya, Social Community, Role